Prevalence of latent tuberculosis infection and feasibility of TB preventive therapy among Thai prisoners: a cross-sectional study - Sivaporn Gatechompol; Weerakit Harnpariphan; Ruamthip Supanan; Gompol Suwanpimolkul; Jiratchaya Sophonphan; Sasiwimol Ubolyam; Stephen J. Kerr; Anchalee Avihingsanon; Kamon Kawkitinarong (BMC, 2021)
Abstract Background Prisons are considered as major reservoirs for tuberculosis. Preventive therapy for latent TB infection (LTBI) is an adjunctive strategy to control TB. However, LTBI data in Thai prisoners is limited. This study assessed the prevalence of LTBI and feasibility of isoniazid preventive therapy (IPT). Methods A cross-sectional study was conducted among prisoners in Klong Prem Central Prison, Bangkok. Participants were screened for active TB by questionnaire and chest X-ray. LTBI was evaluated by Tuberculin skin test (TST) and QuantiFERON-TB Gold Plus (QFTP) among subgroup. Participants with positive TST or QFTP were considered to have LTBI. Participants with LTBI were offered IPT. Results From August 2018-November 2019, 1002 participants were analyzed. All participants were male with a median age of 38 (IQR 32-50) years. LTBI identified by either TST/QFTP was present in 466 (46.5%) participants. TST was positive in 359 (36%) participants. In the subgroup of 294 participants who had both TST and QFTP results, 181/294 (61.6%) tested positive by QFTP. Agreement between TST and QFTP was 55.1% (Kappa = 0.17). The risk factors associated with LTBI were previous incarceration (aOR 1.53, 95%CI, 1.16-2.01, p = 0.002), history of prior active TB (aOR 3.02, 95%CI, 1.74-5.24, p < 0.001) and duration of incarceration ≥10 years (aOR 1.86, 95%CI, 1.24-2.79, p = 0.003). Majority of LTBI participants (82%) agreed to take IPT. Three hundred and 56 (93%) participants completed treatment whereas 27 (7%) participants discontinued IPT due to the side effects of INH. Conclusion This is the first study to evaluate the prevalence of LTBI and feasibility of IPT among Thai prisoners. LTBI prevalence in male prisoners in Thailand is high. LTBI screening and treatment should be implemented together with other preventive components.